2007
DOI: 10.4088/pcc.v09n0504
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Drug Use in Israel

Abstract: Similar to findings in other European countries, our findings suggest that the majority of individuals diagnosed with a common mental disorder are not being treated with psychotropic drugs or are being inappropriately treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
5
0
8
Order By: Relevance
“…The prevalent use of psychotropic medications assessed in this investigation by community dwelling elderly aged 75–94 (24%–28%) is in line with other findings from Israel (Grinshpoon et al, 2007) for elderly aged 70 and over (23%) but higher than reported for ages 65 and over in the U.S. (19%) for all psychotropic prescriptions (Aparasu, Mort, & Brandt, 2003). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalent use of psychotropic medications assessed in this investigation by community dwelling elderly aged 75–94 (24%–28%) is in line with other findings from Israel (Grinshpoon et al, 2007) for elderly aged 70 and over (23%) but higher than reported for ages 65 and over in the U.S. (19%) for all psychotropic prescriptions (Aparasu, Mort, & Brandt, 2003). …”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were observed in The Netherlands where a decreased risk of ADHD medications was shown among Turkish and Moroccan immigrants as compared to the native population (Wittkampf et al, 2010). Lower use of psychotropic medications by Orthodox Jews was also observed in the former mentioned Israeli national study which pointed to the negative attitudes of Orthodox Jews to mental disorders (Grinshpoon et al, 2007). …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The prevalence of overall drug consumption in São Paulo in the 70s was 12.9% [ 4 ], decreasing to 10.6% in the 80s [ 1 ], 7% [ 5 ] in 2002 and then to 8.8% in 2007. Comparing to results from the WHO World Mental Health Surveys vary from, our rates are similar in Spain (16%) [ 35 ], lower than France (21%) [ 36 ], Belgium (19%) [ 37 ], but higher than Israel (7%) [ 38 ], Canada (7%) [ 39 ] and Germany (6%) [ 13 ].…”
Section: Discussionmentioning
confidence: 68%
“…In a series of pharmacoepidemiological studies conducted by the World Mental Health Survey Initiative (WMHS) ( 16 , 17 ), the use of psychotropic agents was evaluated in the general population. In addition, if a respondent had been diagnosed with a psychiatric disorder in the 12 months preceding the survey, this was recorded ( 18 , 19 ). The observed prevalence of BZD use in the general population ranged between 3.2% and 18.6% ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%